From the World of Numbers to the World of Meaning: Husserl's Phenomenological Study of the Spiritual Consciousness of Accounting Students - Salsabila Adi Ahsan; Alimuddin; Syarifuddin (LP2M IAIN Palopo, 2026)
This research explores lived experience and the meaning of spiritual values of final semester students of the Accounting Study Program, University of West Sulawesi. Using Edmund Husserl's phenomenological method, this qualitative research involved six informants of S1 Accounting students in semesters 7–8 who were selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed through époché stages, eidetic reduction, and Husserlian intentional analysis. From the analysis process, five essential themes were found: (1) the transformation of students' awareness of accounting from technical understanding to moral and social responsibility; (2) spiritual values as